Ecocultural Adaptation of the Kadars of Kerala - M.S. Mahendrakumar (Stud. Tribes Tribals, 3(2): 99-104 (2005), 2005)
This article focuses on the ecocultural adaptation and socio-cultural status of a traditional hill dwelling tribe, Kadars, of Kerala. Subsistence activities and sustenance have become the major problems of the Kadars, when their traditional habitat became a Wildlife Sanctuary. The food gathering tribe was forced to change their subsistence activities without an alternative, which resulted in a complex situation wherein the Kadars resist to changes on one hand and on the other hand they face problems in finding out stable support for life and culture. From the etic point of view, the partial isolation is a major hurdle for adequate level of change of subsistence activities whereas from the emic view, the necessity for reinforcement of their traditional rights on forest and way for easy accessibility to the mainstream population for finding out current vocational opportunities are the primary concern of the Kadars